2020
DOI: 10.1364/oe.409076
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of para- and perifoveal photoreceptor densities and the impact of meridians and age in healthy eyes with adaptive-optics optical coherence tomography (AO-OCT)

Abstract: An adaptive optics optical coherence tomography (AO-OCT) system is used to assess sixty healthy eyes of thirty subjects (age 22 to 75) to evaluate how the outer retinal layers, foveal eccentricity and age effect the mean cone density. The cone mosaics of different retinal planes (the cone inner segment outer segment junction (IS/OS), the cone outer segment combined with the IS/OS (ISOS+), the cone outer segment tips (COST), and the full en-face plane (FEF)) at four main meridians (superior, nasal, inferior, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…There is little evidence for cone loss in the ageing primate retina including humans [ 7 , 25 ], although Reumueller et al found a weak reduction in number, but this was from imaging with adaptive optics [ 41 ]. Panda-Jones et al also noted a small decline in cone numbers in human ageing but the scatter in the data was very large [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence for cone loss in the ageing primate retina including humans [ 7 , 25 ], although Reumueller et al found a weak reduction in number, but this was from imaging with adaptive optics [ 41 ]. Panda-Jones et al also noted a small decline in cone numbers in human ageing but the scatter in the data was very large [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on clinical AO-OCT imaging has outlined the importance of high resolution imaging of the retina in three dimensions 42 , 43 . With the instrument we introduce here, commercialization of this technology comes one step closer and possibly triggers a more widespread clinical use of such instruments.…”
Section: Discussionmentioning
confidence: 99%
“…This would explain why PR signal density and morphology in areas with intact capillary perfusion in the diabetic eyes analyzed in the current study were comparable to a larger sample of healthy subjects recently examined with the same AO-OCT prototype. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, we could ensure that intra-individual comparison of PR density values, which are known to decrease with increasing distance from the foveal center, were not influenced by a varying extent of foveal eccentricity. 24 , 25 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation